Ump Intelligent Chatbot Using Dialogflow - Joachim, Agostain (2022)
Advances in artificial intelligence technology allow Chatbot to help with day-to-day affairs. It takes a lot of time and costs to pay up for the salary of customer service, and the availability of customer support is also limited. A chatbot is an automated program that interacts with customers like a human would and cost little to nothing to engage with. To create such a chatbot, a machine learning algorithm is used to learn the human language that is mainly used during such conversations. Natural language keyword phrases put artificial intelligence in chatbots that allow computers to understand how humans talk in normal language. Natural Language keyword phrases are a way for computers to analyze, understand, and derive meaning from human language smartly and usefully. Utilizing the Natural Language keyword phrases model can organize and structure knowledge to perform tasks such as automatic summarization, translation, named entity recognition, relationship extraction, sentiment analysis, speech recognition, and topic segmentation. The chatbot analyses the text input considers the best response and delivers that back to the user. The chatbot’s reply output will be delivered as written text and voice commands. While normal customer service representatives are given manual instructions which they must be thorough with, a customer support chatbot is nourished with many conversation logs, and from those logs, the chatbot can understand what type of questions needs, and what kind of answers. Existing customer service causes a delay in response time because customer support representatives must serve one customer at a time. Whereas chatbots attend to customers at all times of the day and week and are not limited by time or a physical location. A chatbot allows a user to simply ask questions in the same manner that they would address a human. This project aims to develop a chatbot that can answer most questions at University Malaysia Pahang by using the DialogFlow application that uses the Natural Language keyword phrases model in the intent data.